Keugaharian Sebagai Spiritualitas Pastoral Dalam Upaya Gereja Menentang Konsumerisme - Mentari Tarore; Vera Burhan (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2026)
This study explores frugality as a form of pastoral spirituality that serves as a strategic response of the church in resisting the growing culture of consumerism in contemporary society. Consumerism not only shapes the lifestyle of church members but also influences faith orientation, social relationships, and pastoral practice within the church. This research highlights that frugality expressed through simplicity, self-control, and a Christ-centered orientation can function as a transformative spiritual foundation that liberates believers from consumptive patterns of life. The findings indicate that implementing frugality pastorally, through teaching, liturgy, and diaconal practice, fosters critical awareness, ethical transformation, and ecological responsibility among congregations. Thus, frugality is not merely a moral principle but a liberative spirituality that equips the church to fulfill its prophetic role in confronting the challenges of consumerism.